Implementation of the Minister of Home Affairs Regulation on Official Correspondence Guidelines: A Case Study of the East Java Provincial Secretariat - Indah Novia Alfianita; fediantyaugustinah; Dian Ferriswara; Sri Kamariyah; Sanjaya Adi (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
This study aims to analyze the implementation of the Minister of Home Affairs Regulation based on official correspondence guidelines at the East Java Provincial Secretariat. Effective communication and standardized document formats are essential for promoting transparency, accountability, and professionalism in public administration. A qualitative research approach was employed, with data collected through direct observation and analysis of 15 official documents to evaluate the extent of guideline application. The findings indicate that the policy has not been fully implemented, with key challenges including limited understanding of the guidelines, inadequate training and socialization for administrative personnel, and resistance to adopting standardized procedures. These issues hinder the consistency and clarity of official communication. To address these barriers, regular policy evaluations, structured training programs, and strong leadership support are recommended. The study implies that reinforcing standardized correspondence practices can significantly enhance administrative efficiency and institutional governance.